Pelatihan Majalah Dinding Digital Berbasis Web bagi Komunitas Seni Hysteria Semarang - Wardani, Theodora Indriati; Kusmantoro, Adhi; Farikhah, Irna; Purwosetiyono, FX. Didik (Perkumpulan Kualitama Edukatika Indonesia, 2024)
In the city of Semarang along with the development of the city of Semarang as the number five big city in Indonesia, communities have sprung up that have special activities as activities to foster love for the city of Semarang, namely for the future development of the city of Semarang. One of them is the Hysteria community based in Semarang who works for the city of Semarang. Hysteria Community, a community from Semarang. In the management of Hysteria each member of the board has a personal network and that personal network consists of literati, artists, painters, music artists, journalists, art students, choreographers, dance artists, but when their activities have been carried out and information in the form of pictures and writings must be displayed or shown to other people or the public around where they are active or working, They still make wall magazine designs. In the development of the digital technology era requires expertise and skills in the field of communication technology, the wall magazines that are still made by the Hysteria art community are usually still manual or conventional, namely in the form of a collection of wall magazine materials (mading) that are pasted and arranged in such a way on one large sheet of paper of rather thick size, so that the information in the wall magazine (mading) is not widely spread and requires costs, time and energy to make the wall magazine, so there is a waste of costs, so it was thought of how members of the Hysteria art community can independently use the application to disseminate wall magazine information (mading) to convey information on activities using a digital-based internet network in the form of a website to make it more attractive, so it is necessary to carry out a community partnership program, namely holding a web-based digital mading (wall magazine) training using the Google Sites software application without using paper pasted on the wall to reduce waste of cost, time and energy, and accelerate the dissemination of information using internet facilities for the Hysteria art community network spread across the city of Semarang.